LAW ENFORCEMENT ON OVERLOADING OF MINIBUS TAXIS IN MAPUTO - Seda, Fulgêncio Lucas Muti (My University, 2011)
This study was conducted in Maputo, the capital of Mozambique. The context of this study is the imbalance facing the transport industry in Maputo. This disparity relates to the forces of supply and demand between the public and private sectors in the provision of a healthy transport service. The overloading of passengers was identified as the primary research problem, and was linked to two management functions: leadership and control. The purpose of the study was to investigate the factors leading to overloading, the dominant trends in the enforcement of regulations on overloading, and the current government strategy (if any) to address the problem. The study applied a qualitative method in which inter-departmental interviews were conducted with the taxi drivers, passengers, traffic officials and representatives of the government. Findings indicated that the private sector has dominated the transport industry and that this situation has resulted in high demands being placed on transport. A result of these demands is overloading as an ineffective enforcement body is attempting to develop a form of intervention in the face of conflicting political influences. This study concludes by recommending a complete transformation of the transport industry. New rules should be introduced which prohibit government members from owning minibus taxis that are used for public transport. The aim of this would be to considerably reduce political influence. Consequently, an effective enforcement body would act to protect passengers from opportunistic private operators
MM - P&DM
Keywords: Minibus taxis; Maputo; Mozambique